ĐIỀU KIỆN NỀN ĐẤT ẢNH HƯỞNG BỞI TÁC ĐỘNG ĐỘNG ĐẤT KHU VỰC PHÍA TÂY NỘI THÀNH HÀ NỘI - Bắc, Trịnh Việt; Toàn, Đinh Văn; Phòng, Lại Hợp; Vũ, Trần Anh (Vietnam Journal of Earth Sciences, 2012)
Site condition on the western urban area of Hanoi cityRecently, high building constructions were blossomed in the western urban area of Hanoi city. Coming with that, site condition investigations was carried out in this area to support seismic resistance design. According to seismic design standard for construcions, shear velocity Vs,30 is standard value to classify soil site. Owing to 37 vertical seismic profile investigations in the western urban area of Hanoi city, the authors introduced some soil characteristics of the site. These results contribute significantly to seismic resistance design of constructions.